2022
DOI: 10.1001/jamapediatrics.2022.1510
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Socioeconomic Disadvantage With Missed Telemedicine Visits for Pediatric Patients During the COVID-19 Pandemic

Abstract: Missed scheduled clinic appointments (ie, no-shows) are more common among uninsured patients from racial and ethnic minority groups living in economically disadvantaged areas and contribute to poorer health outcomes. [1][2][3] In the pediatric population, the implications of telemedicine for no-show rates have not been adequately explored despite the widespread adoption of telemedicine during the COVID-19 pandemic. The aim of this study was to ascertain whether patient race and ethnicity and level of socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Despite the improved overall no-show rates, one recent pediatric gastroenterology study during the COVID-19 pandemic showed that patients classified as lower socioeconomic status had a 4 × higher odds of no-show visits compared to higher socioeconomic status patients. Additionally, patients with a higher probability of economic disadvantage were associated with a 5 × increased odds of no-show for telemedicine visits compared to in-person visits [ 14 ]. Thus, it will be important moving forward in pediatric subspecialties to help facilitate telemedicine or in-person clinic visits (easier scheduling, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the improved overall no-show rates, one recent pediatric gastroenterology study during the COVID-19 pandemic showed that patients classified as lower socioeconomic status had a 4 × higher odds of no-show visits compared to higher socioeconomic status patients. Additionally, patients with a higher probability of economic disadvantage were associated with a 5 × increased odds of no-show for telemedicine visits compared to in-person visits [ 14 ]. Thus, it will be important moving forward in pediatric subspecialties to help facilitate telemedicine or in-person clinic visits (easier scheduling, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, to determine neighborhood-specific socioeconomic status, ArcGIS Pro (Esri, Redlands, California) was used to geocode patients’ addresses at diagnosis into their corresponding census tracts, and then calculated the ADI score for each census tract [ 11 Oluyomi]. The ADI is a composite measure of neighborhood deprivation developed and validated by Singh, which relies on 17 weighted indicators drawn from four categories of the US Census American Community Survey (ACS) 5-year estimates: poverty, housing, employment, and education (Supplementary Table 1) [ 12 14 ]. Census tracts were then divided into high vs low ADI score distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the improved overall no-show rates, one recent pediatric gastroenterology study during the COVID-19 pandemic showed that patients classi ed as lower socioeconomic status had a 4x higher odds of no-show visits compared to higher socioeconomic status patients. Additionally, patients with a higher probability of economic disadvantage were associated with a 5x increased odds of no-show for telemedicine visits compared to in-person visits [11]. Thus it will be important moving forward in pediatric subspecialties to help facilitate telemedicine or in-person clinic visits (easier scheduling, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Populations already at risk for health care disparities have been found to be more prone to missed care opportunities with a greater reliance on audio-only telephone-based visits. [7][8][9] Phone encounters may be more feasible in some settings, but lack the same level of providerpatient engagement and monitoring afforded by video modalities. 10 Altogether, internet connectivity has become increasingly recognized as a social determinant of health.…”
Section: Background and Significancementioning
confidence: 99%